POWER OFMICROCREDIT TO REMOVE THE GLOBAL POVERTY - Nazmul Hossain (European Scientific Journal, ESJ, 2014)
The total world population is 7.093 billion of them 1.29 billion do live with absolute poverty [PPP below $1.25]. Around 4 million of people die cause of starving and malnutrition and 25 million without treatment/year. 100 million is homeless and further 100 million is hidden homeless. Around 200 million is unemployed, of them 75 million that is 13% of the total figure is between the ages of 15 & 24 [IMF-2012]. If dramatic changes are not happened in the world job markets and young jobless is remain stable, its impact would be very devastative for the forthcoming world.